2017
DOI: 10.3389/fmicb.2017.00778
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of Sugarcane Smut Disease by Interference of Fungal Sexual Mating and Hyphal Growth Using a Bacterial Isolate

Abstract: Sugarcane smut is a fungal disease caused by Sporisorium scitamineum, which can cause severe economic losses in sugarcane industry. The infection depends on the mating of bipolar sporida to form a dikaryon and develops into hyphae to penetrate the meristematic tissue of sugarcane. In this study, we set to isolate bacterial strains capable of blocking the fungal mating and evaluate their potential in control of sugarcane smut disease. A bacterial isolate ST4 from rhizosphere displayed potent inhibitory activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…campestris Xc1 Pathogen of crucifers black rot [ 69 ] 9.68 ± 0.36 0 0 0 Pseudomonas aeruginosa PAO1 Pathogen of cystic fibrosis [ 70 ] 4.04 ± 0.43 0 0 0 Fusarium oxysporum f.sp. cubense FOC4 Pathogen of banana wilt [ 71 ] 6.17 ± 0.33 3.95 ± 0.39 3.32 ± 0.22 0 Rhizoctonia solani AG-1 IA Pathogen of rice sheath blight [ 72 ] 4.07 ± 0.23 1.31 ± 0.09 0.70 ± 0.15 0 Magnaporthe oryzae B157 Pathogen of rice blast [ 73 ] 4.70 ± 0.28 1.98 ± 0.34 1.50 ± 0.31 0 Peronophythora litchi Pathogen of litchi downy blight [ 74 ] 11.69 ± 0.34 8.71 ± 0.15 3.48 ± 0.21 3.72 ± 0.22 Colletotrichum capsici Pathogen of capsicum anthracnose Lab storage 5.45 ± 0.14 5.26 ± 0.13 4.79 ± 0.10 0 C. gloeosporioides Pathogen of mango anthracnose Lab storage 4.91 ± 0.10 4.06 ± 0.20 3.59 ± 0.42 0 Sporisorium scitamineum Pathogen of sugarcane smut [ 75 ] 2.60 ± 0.06 2.27 ± 0.54 1.51 ± 0.22 0 …”
Section: Resultsmentioning
confidence: 99%
“…campestris Xc1 Pathogen of crucifers black rot [ 69 ] 9.68 ± 0.36 0 0 0 Pseudomonas aeruginosa PAO1 Pathogen of cystic fibrosis [ 70 ] 4.04 ± 0.43 0 0 0 Fusarium oxysporum f.sp. cubense FOC4 Pathogen of banana wilt [ 71 ] 6.17 ± 0.33 3.95 ± 0.39 3.32 ± 0.22 0 Rhizoctonia solani AG-1 IA Pathogen of rice sheath blight [ 72 ] 4.07 ± 0.23 1.31 ± 0.09 0.70 ± 0.15 0 Magnaporthe oryzae B157 Pathogen of rice blast [ 73 ] 4.70 ± 0.28 1.98 ± 0.34 1.50 ± 0.31 0 Peronophythora litchi Pathogen of litchi downy blight [ 74 ] 11.69 ± 0.34 8.71 ± 0.15 3.48 ± 0.21 3.72 ± 0.22 Colletotrichum capsici Pathogen of capsicum anthracnose Lab storage 5.45 ± 0.14 5.26 ± 0.13 4.79 ± 0.10 0 C. gloeosporioides Pathogen of mango anthracnose Lab storage 4.91 ± 0.10 4.06 ± 0.20 3.59 ± 0.42 0 Sporisorium scitamineum Pathogen of sugarcane smut [ 75 ] 2.60 ± 0.06 2.27 ± 0.54 1.51 ± 0.22 0 …”
Section: Resultsmentioning
confidence: 99%
“…Pseudomonas sp. ST4 displayed a potent inhibitory activity on the sexual mating of S. scitamineum, and evidence suggests that the active components are small molecules diffusible in PDA agar medium (Liu et al ., ). Thermal stability assay showed that Pseudomonas sp.…”
Section: Resultsmentioning
confidence: 97%
“…ST4 slightly reduced the disease occurrence, with a disease incidence at about 89%. However, similar to the case of sugarcane trials (Liu et al ., ), when Pseudomonas sp. ST4 grew and inoculated with 2% glucose, its biocontrol efficiency was greatly increased with a disease incidence reduced to only about 15% (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…produce alphahydroxy-ketones; and Xylella fastidiosa and Xanthomonas spp. produce a wide variety of diffusible signal factors (DSFs) (Flavier et al, 1997;Chen et al, 2002;Kendall and Sperandio, 2007;Zhang et al, 2007;Mei et al, 2010;Churchill and Chen, 2011;Winans, 2011;Lee and Zhang, 2015;Ryan et al, 2015;Liu et al, 2017;Zhan et al, 2018). DSF is widely conserved in gram-negative bacterial pathogens (Deng et al, 2011;Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%